2012
DOI: 10.1126/science.1224839
|View full text |Cite
|
Sign up to set email alerts
|

Active DNA Demethylation in Plant Companion Cells Reinforces Transposon Methylation in Gametes

Abstract: The Arabidopsis thaliana central cell, the companion cell of the egg, undergoes DNA demethylation before fertilization, but the targeting preferences, mechanism, and biological significance of this process remain unclear. Here, we show that active DNA demethylation mediated by the DEMETER DNA glycosylase accounts for all of the demethylation in the central cell and preferentially targets small, AT-rich, and nucleosome-depleted euchromatic transposable elements. The vegetative cell, the companion cell of sperm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
753
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(810 citation statements)
references
References 30 publications
41
753
3
2
Order By: Relevance
“…Consistent with these data, we found strong enrichment of H3K27m3 on genes showing increased expression levels in triploid seeds compared with diploid seeds ( Figure 7A). Loss of FIS-PRC2 function in the endosperm causes strikingly similar changes of DNA methylation, as we report in this study: reduced levels of CHG and CHH methylation and increased levels of CG methylation (Ibarra et al, 2012). Previous studies revealed that hypomethylated pollen derived from a MET1 antisense plant can bypass maternal FIS-PRC2 requirement (Luo et al, 2000;Vinkenoog et al, 2000).…”
Section: Suppression Of the Triploid Block By Met1-induced Paternal Gsupporting
confidence: 67%
“…Consistent with these data, we found strong enrichment of H3K27m3 on genes showing increased expression levels in triploid seeds compared with diploid seeds ( Figure 7A). Loss of FIS-PRC2 function in the endosperm causes strikingly similar changes of DNA methylation, as we report in this study: reduced levels of CHG and CHH methylation and increased levels of CG methylation (Ibarra et al, 2012). Previous studies revealed that hypomethylated pollen derived from a MET1 antisense plant can bypass maternal FIS-PRC2 requirement (Luo et al, 2000;Vinkenoog et al, 2000).…”
Section: Suppression Of the Triploid Block By Met1-induced Paternal Gsupporting
confidence: 67%
“…These findings are consistent with studies of mammalian genes, where hypomethylation of gene-regulatory regions is commonly observed at sites of DNA-protein interaction 8 . Interestingly, the authors observe very little change in DNA methylation state on transposable elements during fruit maturation, in stark contrast to the novel developmental demethylation events recently reported in the endosperm and pollen of Arabidopsis, which occur mainly on transposable elements 9,10 .…”
contrasting
confidence: 72%
“…The second model proposes spermatocyte-specific transcriptional reprogramming by global chromatin changes and transcriptional activation of retrogenes and their subsequent functionalization specific to spermatocytes (Marques et al, 2005;Potrzebowski et al, 2008). In plants, pollen has been identified as the hotspot of chromatin reprogramming (Slotkin et al, 2009;Ibarra et al, 2012;Hoffmann and Palmgren, 2013), and we have shown that pollen upregulated genes are depleted from transcription-permissive chromatin marks in somatic tissues. Furthermore, we found several retrogenes that are associated with pollen growth and development and the PCR11 retrogene, which is transcribed in pollen, contrary to its parent.…”
Section: Retrogenes Are Preferentially Upregulated In Pollenmentioning
confidence: 99%
“…More likely, many retrogenes are part of global cellular reprogramming in male gametes. So far, chromatin changes in male gametes have been associated mainly with DNA methylation changes (Slotkin et al, 2009;Ibarra et al, 2012), but there is emerging evidence that histone modifications may also contribute to pollen-specific gene reprogramming (Hoffmann and Palmgren, 2013). In order to identify possible causes of the observed pollen-specific transcription, we explored available data on tissue-and mutant-specific transcription and the distribution of chromatin modifications.…”
Section: Retrogenes Are Preferentially Upregulated In Pollenmentioning
confidence: 99%
See 1 more Smart Citation